2002
DOI: 10.1046/j.1523-1739.2002.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Abilities of Rare and Common Plants: Comparisons UsingAcaena(Rosaceae) andChionochloa(Poaceae) from New Zealand

Abstract: It is commonly suggested that rare plant species are poor competitors. However, the study of rarity and competitive ability has, like much of the research on rare species, been hindered by insufficient sample size, scarce use of experimental methods, and lack of comparison with common species. We used a within‐taxon comparative approach to test for differences in competitive ability between rare and common species in two genera, Acaena ( Rosaceae: six rare and four common species) and Chionochloa ( Poaceae: fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…Yet theory has historically emphasized the importance of competitive interactions in invasions (Parker and Reichard 1998), and when invasive plants appear to suppress native ones competition is often presumed to be the cause. This is particularly likely to be the case for rare and endemic plants, which are often stereotyped as poor competitors, even in the absence of evidence that they necessarily have lower competitive ability than common congeners (Lloyd et al 2002;Brigham 2003). Case studies such as this one suggest more caution in making the oftenunexamined assumption that invasive plant impacts result primarily from resource competition, as well as greater attention to mechanistic studies of native-invasive plant interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Yet theory has historically emphasized the importance of competitive interactions in invasions (Parker and Reichard 1998), and when invasive plants appear to suppress native ones competition is often presumed to be the cause. This is particularly likely to be the case for rare and endemic plants, which are often stereotyped as poor competitors, even in the absence of evidence that they necessarily have lower competitive ability than common congeners (Lloyd et al 2002;Brigham 2003). Case studies such as this one suggest more caution in making the oftenunexamined assumption that invasive plant impacts result primarily from resource competition, as well as greater attention to mechanistic studies of native-invasive plant interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Vegetation on rock outcrops is usually dominated by narrow (shallow soil) endemic species, with the coexistence of widespread species (Baskin and Baskin 1988;Walck et al 1999). There has been a growing interest in comparing the competitive ability between narrow endemic and widespread species (Snyder et al 1994;Walck et al 1999;Osunkoya and Swanborough 2001;Lloyd et al 2002;Imbert et al 2012). Some experiments have confirmed a low competitive ability for endemic species (Walck et al 1999;Lloyd et al 2002), while other studies have shown that the endemic has a greater competitive ability than the widespread species (Snyder et al 1994;Osunkoya and Swanborough 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Rare species can be inferior competitors (Walck et al 1999;Binney and Bradfield 2000;Lavergne et al 2003;Moora et al 2003), roughly equivalent competitors (Snyder et al 1994;Ru¨nk et al 2004) or even superior competitors (Rabinowitz et al 1984). Lloyd et al (2002) investigated experimentally the largest species sample so far and received mixed results. They concluded that although rare species may have a low competitive ability in certain cases, this should not be assumed to be a uniform cause of rarity.…”
Section: Introductionmentioning
confidence: 99%